2021
DOI: 10.1007/s10880-021-09813-0
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Strategies to Minimize Procedural Distress During In-Office Pediatric Tympanostomy Tube Placement Without Sedation or Restraint

Abstract: The purpose of this study was to evaluate behavioral strategies to minimize procedural distress associated with in-office tympanostomy tube placement for children without general anesthesia, sedation, or papoose-board restraints. 120 6-month- to 4-year-olds and 102 5- to 12-year-olds were treated at 16 otolaryngology practices. Mean age of children was 4.7 years old (SD = 3.18 years), with more boys (58.1%) than girls (41.9%). The cohort included 14% Hispanic or Latinx, 84.2% White, 12.6% Black, 1.8% Asian and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
0
2
2
Order By: Relevance
“…Unfortunately, due to limited resources, child life specialists were rarely present during the under LA, which would likely improve the overall experience. It has been demonstrated that parental presence, the use of neutral language, a calm attitude, and information about procedural steps reduce children's anxiety 25 . However, in our study, parental presence has not been associated with a decrease in pain scores.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Unfortunately, due to limited resources, child life specialists were rarely present during the under LA, which would likely improve the overall experience. It has been demonstrated that parental presence, the use of neutral language, a calm attitude, and information about procedural steps reduce children's anxiety 25 . However, in our study, parental presence has not been associated with a decrease in pain scores.…”
Section: Discussioncontrasting
confidence: 87%
“…It has been demonstrated that parental presence, the use of neutral language, a calm attitude, and information about procedural steps reduce children's anxiety. 25 However, in our study, parental presence has not been associated with a decrease in pain scores. Music can also reduce anxiety and pain for some children undergoing clinical procedures, 26 but has not influenced our results.…”
Section: Discussioncontrasting
confidence: 74%
“…The evolution of national guidelines, standardized definitions of the depth of sedation and outcomes, and the application of non-pharmacologic techniques have further contributed to reducing the risk of significant adverse events [17]. Once common practices such as immobilization through papoosing (physically restraining a child to keep children still during the medical procedure) have almost universally been replaced with distraction techniques that range from the rudimentary (a book) to the more sophisticated (tablet) [18].…”
Section: Introductionmentioning
confidence: 99%
“…A system of technologies (Tula® System; Smith & Nephew) was designed consisting of iontophoresis for the administration of a local anesthetic (2% lidocaine/1:100,000 epinephrine; TYMBION™; Smith & Nephew) to the tympanic membrane (TM), and automated tube delivery that integrates myringotomy and tube placement. Clinical research established the safety, efficacy, and tolerability of this system for in‐office procedures in children, 18‐20 and its use has been further supported in adults 21 . The Tula System was granted breakthrough designation and received US Food and Drug Administration (FDA) approval in 2019 for in‐office tympanostomy in children ages 6 months and older and adult patients.…”
mentioning
confidence: 99%